Effects of 3D culturing conditions on the transcriptomic profile of stem-cell-derived neurons. (July 2018) - Tekin, Halil; Simmons, Sean; Cummings, Beryl; Gao, Linyi; Adiconis, Xian; Hession, Cynthia; Ghoshal, Ayan; Dionne, Danielle; Choudhury, Sourav; Yesilyurt, Volkan; Sanjana, Neville; Shi, Xi; et al.
Abstract Understanding neurological diseases requires tractable genetic systems, and engineered three-dimensional (3D) neural tissues are an attractive choice. Yet how the cellular transcriptomic profiles in these tissues are affected by the encapsulating materials and are related to the human brain transcriptome is not well understood. Here, we report the characterization of the effects of different culturing conditions on the transcriptomic profiles of induced neuronal cells and developed a method for the rapid generation of 3D co-cultures of neuronal and astrocytic cells from the same pool of human embryonic stem cells. By comparing the gene-expression profiles of neuronal cells in culture conditions relevant to the developing human brain, we found that modifying the degree of crosslinking of composite hydrogels can tune expression patterns so that they correlate with those of specific brain regions and developmental stages. Moreover, single-cell-sequencing results showed that our engineered tissues recapitulate transcriptional patterns of cell types in the human brain. Analyses of culturing conditions will inform the development of 3D neural tissues for use as tractable models of brain diseases. Culturing conditions affect the transcriptomic profiles of induced neuronal cells, and 3D co-cultures of induced neuronal cells and astrocytic cells can be rapidly generated from the same pool of human embryonic stem cells.